Beyond the Motor Cortex: Thalamic Iron Deposition Accounts for Disease Severity in Amyotrophic Lateral Sclerosis - Li, Qianwen; Zhu, Wenjia; Wen, Xinmei; Zang, Zhenxiang; Da, Yuwei; Lu, Jie (Frontiers in Neurology, 2022)
Objective Previous studies have reliably identified iron deposition in the motor cortex as potential pathogenesis of amyotrophic lateral sclerosis (ALS). Here, we intended to investigate iron deposition, gray matter (GM) atrophy, and their associations with disease severity in the motor cortex and the thalamus in patients with ALS. Methods A total of 34 patients with ALS (age 51.31 ± 8.24 years, 23 males) and 34 nonneurological controls (age 50.96 ± 9.35 years, 19 males) were enrolled between 2018 and 2020. The Revised ALS Functional Rating Scale (ALSFRS-R) and the Penn upper motor neuron (UMN) score were measured. MRI data included quantitative susceptibility mapping (QSM) for iron deposition and three-dimensional (3D) T1 for gray matter volume. After a between-group comparison, Pearson's correlation coefficient was used for identifying correlations of iron deposition, GM volume, and clinical measurements. Results The two-sample t-tests revealed increased iron deposition in the left precentral gyrus (peak voxel T = 4.78, PSVC = 0.03) and the thalamus (peak voxel: right: T = 6.38, PSVC < 0.001; left: T = 4.64, PSVC = 0.02) in patients with ALS. GM volume of the precentral gyrus (T = −2.42, P = 0.02) and the bilateral thalamus (T = −4.10, P < 0.001) were reduced. Negative correlations were found between the increased QSM values and the decreased GM volume (P < 0.04, one-tailed) in patients with ALS. Iron deposition in the left precentral gyrus was positively correlated with the UMN score (R = 0.40, P = 0.02) and the GM volume was negatively correlated with the UMN score (R = −0.48, P = 0.004). Negative correlation between thalamic iron deposition and the ALSFRS-R (R = −0.36, P = 0.04) score was observed. Discussion Iron deposition in the thalamus, in addition to the motor cortex, is accompanied by GM atrophy and is associated with disease severity in patients with ALS, indicating that the thalamus is also a pathological region in patients with ALS.